Water-induced local ordering of chitosan polymer chains in thin layer films. (15th March 2015) - Madeleine-Perdrillat, Claire; Karbowiak, Thomas; Raya, Jesus; Gougeon, Régis; Bodart, Philippe R.; Debeaufort, Frédéric
Graphical abstract: Highlights: Chitosan salt films synthesized in acetic acid medium. Spontaneous removal of acetic acid by increasing the moisture content. Multiplicity of signals for carbon atoms implied in the glycosidic linkage. Different water-induced conformational states. Abstract: Carbon-13 NMR (CP-MAS and FSLG 1 H– 13 C HETCOR) have been applied to chitosan salt films synthesized in acetic acid and exposed to different relative humidity environments (32% or 75%) at 20 °C for 1 month. It gives insight in the relationship between structure and functional properties according to the hydration level of this biomaterial as a film. The acetate ions trapped in the chitosan act as structuring agents between chitosan chains for the low hydration state. But, increasing the moisture content induces spontaneous removal of acetic acid and a subsequent modification in the film structure, with an increase in local ordering. HETCOR experiments also showed a multiplicity of signals for most of the observed carbon atoms and in particular those implied in the glycosidic linkage, which reveals different water-induced conformational states. Changing the water content allows to modify the polymer structure and therefore to modulate the properties such as controlled release of active compounds trapped in chitosan-based coatings, e.g., for medicated dressing or active packaging.